Pembelajaran PAI bagi Peserta Didik Tunanetra di SLB Negeri Wiradesa Kabupaten Pekalongan - Sholikhah, Dyah Ayu; Puspandhari, Siti; Ramadhan, Fachreza Prima; Safi’i, Imam (Lembaga Yasin AlSys, 2022)
Education is very important for humans to achieve social welfare, including students with special needs. Students with special needs have an identity that is not the same as other normal students. Students who have abnormalities in the eye are called blind children. The disorder that cannot see this occurs due to genetic factors and accident factors. This study aims to determine the concept of PAI learning for SLB Negeri Wiradesa, Pekalongan Regency. This study used descriptive qualitative method. The results showed that there was no significant difference in the implementation of learning Islamic religious education at SLB Negeri Wiradesa Pekalongan Regency from other regular schools, the material taught was the same, and the methods used were adapted to the material being taught. Educators need to use learning methods that are different from children in general and are required to be creative in organizing learning because in one class students have different backgrounds.